2021
DOI: 10.3390/healthcare9111606
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Mindfulness-Based Education Program on Brain Waves and the Autonomic Nervous System in University Students

Abstract: Background: Mindfulness, defined as the awareness emerging from purposefully paying attention to the present moment, has been shown to be effective in reducing stress and, thus, promoting psychological well-being. This study investigated the effects of a mindfulness-based education program on mindfulness, brain waves, and the autonomic nervous system (ANS) in university students in Korea. Methods: This study is a quantitative and experimental research with a single-group pre-post design. Six sessions of mindfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…Moreover, the EEG analysis showed that there were significant differences between the students before and after BMI ( p -values < 0.05) in resting states (e.g., eyes-closed and eyes-opened) and tasks (e.g., video stimulation and the Stroop task). These results support the EEG studies that reported significant differences between university students before and after mindfulness, represented by an increase in the alpha and theta and a decrease in the beta rhythms [ 34 ]. However, our study accounted for neuroticism, which has been suggested as a significant factor for studying the impact of mindfulness [ 23 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Moreover, the EEG analysis showed that there were significant differences between the students before and after BMI ( p -values < 0.05) in resting states (e.g., eyes-closed and eyes-opened) and tasks (e.g., video stimulation and the Stroop task). These results support the EEG studies that reported significant differences between university students before and after mindfulness, represented by an increase in the alpha and theta and a decrease in the beta rhythms [ 34 ]. However, our study accounted for neuroticism, which has been suggested as a significant factor for studying the impact of mindfulness [ 23 ].…”
Section: Discussionsupporting
confidence: 89%
“…The attempt to identify an EEG channel to evaluate the effect of mindfulness is an ever-growing interesting research area. There are EEG devices that have been used to improve education through mindfulness with one [ 33 ] or more channels [ 34 ]. Using simple, relatively low-cost equipment may help neurotic students to evaluate the effect of mindfulness and encourage them to keep consistent practice, and therefore facilitate healthy life-style monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…These results reveal that mindfulness training elevated the brain waves that signify a state of relaxed awareness. Jung et al (2021) examined the effects of a mindfulness-based education program on mindfulness, brain waves, and the autonomic nervous system in university students. After six sessions of mindfulness-based interventions, measures of brain waves indicated an increase in the alpha and theta waves and a decrease in the beta waves.…”
Section: Effects Of Mindfulness Practices On Brain Activitymentioning
confidence: 99%
“…The mindfulness process could make the students more open and honest about themselves, relaxed and flexible. In general, mindfulness researches show that mindfulness could improve learning because the students' behavior toward learning is different, making them more relaxed and peaceful (Bazzano et al, 2018;Jung & Lee, 2021;Semple et al, 2017). The researchers do not show how mindfulness happens to build the inner voice of the learners.…”
Section: Introductionmentioning
confidence: 96%